Working Hours Dan Disiplin Kerja Serta Dampaknya Pada Kinerja Karyawan - Siti Asriah Immawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
The purpose of this study is to determine the impact of working hours and work discipline on employee performance at PT XXX. The sample in this study was 80 employees. The analysis technique used multiple linear regression. The results of the study show that working hours have a negative impact on employee performance, this shows that if working hours are higher, employee performance will be lower, and if working hours decrease, employee performance will increase. Discipline has a positive impact on employee performance, so that increasing employee discipline will be followed by an increase in employee performance.